Analysis of the reverberations of the psychosocial intervention “Construindo Caminhos” in the prison system (Research, Society and Development, 2024)
Prison sentences reach alarming levels in Brazil, amplifying psychosocial vulnerabilities. It is considered that group psychosocial interventions with this population are necessary, especially to mitigate health risks. Therefore, the present study, of mixed character, sought to evaluate the feasibility of the psychosocial intervention “Construindo Caminhos”. The analyzes carried out considered the perspectives of different actors: eight men deprived of their liberty who participated in the 10 group meetings and four penitentiary agents who worked in the place. Data were accessed through interviews, quantitative instruments and field diaries, in addition to the content of books produced by the participants. Satisfaction with the intervention, change in narratives and perceptions about oneself and others were identified; the construction of future planning and the increase in the feeling of well-being. Prison officers showed that they perceived a change in the behavior of the participants after the intervention and considered it to be an important and necessary activity in the prison context, although they also expressed discomfort regarding the changes in routine caused by the intervention. As for the quantitative aspects measured in those deprived of liberty, only individual, but contradictory, changes were identified in relation to aspects of emotional regulation, increased assertive interpersonal behavior and anger expression and management. It is possible to consider that Construindo Caminhos is a viable health promotion intervention for the Brazilian prison system, as it promotes protective factors, which are important to mitigate damage and prevent health risks, which are potentiated by incarceration. Such indicators are preliminary, lacking randomized clinical trials to assess the effectiveness and effectiveness of the intervention.